RESEARCH METHODOLOGIES USED IN PAKISTANI ELT RESEARCH (2015–2025):A PRISMA–SPIDER SYSTEMATIC LITERATURE REVIEW (Contemporary Journal of Social Science Review, 2025)
This is a systematic literature review that investigates the research methodologies of Pakistani research publications in the field of English Language Teaching (ELT) between 2015 and 2025. Instead of discussing a single instructional intervention, the article discusses the way that Pakistani ELT knowledge has been produced: the research designs employed, populations sampled, instruments used, forms of analysis reported, and methodological strengths and gaps. The review mapped empirical studies, applied reports, book chapters and other doctoral-level research that focused on ELT, ESL/EFL learning, language-teaching, assessment, classroom-practice, teacher-development, writing, use of technology, bilingualism or other related English-education issues in Pakistan guided by PRISMA 2020 reporting principles and organized through the SPIDER framework. The screening process identified 415 records, eliminated 103 duplicates/overlaps, screened 312 records, and included 32 studies/reports in qualitative synthesis. The synthesis demonstrates that Pakistani ELT research is methodologically active but uneven. Most of the studies are based on questionnaire surveys, small-scale interviews or mixed-method design that combines Likert-scale questionnaires with semi-structured interviews. More rigorous research involves classroom observations, document reviews, action research, proficiency tests, focus groups or longitudinal classroom intervention, but these are less prevalent. The evidence base is dominated by higher education and teacher perceptions and underrepresented are primary/secondary classrooms, rural settings, public-sector schools, longitudinal learning outcomes, and experimentally tested classroom methods. The review suggests that future research in ELT in Pakistan should go beyond the perception-intensive designs and become more robust with triangulation, clear sampling, validated measures, classroom observations, evidence of learner-performance and open coding frameworks and ethics-based reporting. The article presents a methodological guideline towards enhancing ELT research in Pakistan over the coming 10 years.